Standardisation of indicators of quality of products cognitive technologies - Antsyferov, S.S. (Искусственный интеллект, 2014)
The standard set of quality indicators, reflecting the principal features of functioning and development of
intellectual systems is proposed. Comparative assessment of some of them is given. Запропонована стандартна сукупність показників якості, що відбиває принципові особливості функціонування і розвитку інтелектуальних систем. Дана порівняльна оцінка деяких з них. Предложена стандартная совокупность показателей качества, отражающая принципиальные особенности
функционирования и развития интеллектуальных систем. Дана сравнительная оценка некоторых из них.